2021
DOI: 10.3390/catal11030344
|View full text |Cite
|
Sign up to set email alerts
|

Transition Metal B-Site Substitutions in LaAlO3 Perovskites Reorient Bio-Ethanol Conversion Reactions

Abstract: LaAlO3 perovskites, as such and with 25% molar Al substitution by Cu, Co, or Ga, have been prepared by sol-gel methods and tested as heterogeneous catalysts in the gas-phase conversion of ethanol. LaAlO3 presented a significant acidic character, with high formation of ethylene by ethanol dehydration. B-site substitutions increased the basicity of the catalysts, favoring the dehydrogenation of ethanol to acetaldehyde. The most reducible Cu- and Co-substituted materials, characterized by easier formation of surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 98 publications
(115 reference statements)
0
9
0
Order By: Relevance
“…It was observed that the cell parameters of LFAO-3 decreased, i.e., the smaller radius of Al 3+ ( r Al = 0.39) took the place of the larger radius of Fe 3+ ( r Fe = 0.55), which may result in a decrease in the sample particle size . The lattice parameters of V-LFAO-3 were further reduced, and the crystal distortion rate further increased, indicating that oxygen defects affect crystal growth during sintering …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was observed that the cell parameters of LFAO-3 decreased, i.e., the smaller radius of Al 3+ ( r Al = 0.39) took the place of the larger radius of Fe 3+ ( r Fe = 0.55), which may result in a decrease in the sample particle size . The lattice parameters of V-LFAO-3 were further reduced, and the crystal distortion rate further increased, indicating that oxygen defects affect crystal growth during sintering …”
Section: Resultsmentioning
confidence: 99%
“…38 The lattice parameters of V-LFAO-3 were further reduced, and the crystal distortion rate further increased, indicating that oxygen defects affect crystal growth during sintering. 41 The sample exhibits slight absorption peaks at ∼3440, 1630 cm −1 , and 1460 cm −1 which are attributed to the stretching of −OH groups of water, the bending vibration of H−O−H, and the stretching vibration of C−O, respectively (Figure 1c). 42 The vibration bands of 535 and 418 cm −1 (Figure 1d) belonged to the tensile vibration of Fe−O and the stretching vibration of O−Fe−O, respectively.…”
Section: Physicochemical Properties Of Lafe 1−x Almentioning
confidence: 99%
“…The application in thermal barrier coatings was also considered, whereby layered perovskites of so-called Ruddlesden–Popper structure have an exceptional low thermal conductivity . Chemical, combustion-, , environmental, , , photo-, , and electrocatalysis are other areas of potential use. , , Electrocatalysis includes high-temperature solid-oxide electrolysis cells and water splitting. Photocatalysis includes water splitting , and CO 2 conversions . Emery et al performed a computational screening of perovskites for the solar-driven thermochemical splitting of water, resulting in 139 promising candidates.…”
Section: Lanthanum Monoaluminate (Lma)mentioning
confidence: 99%
“…[11] Among various perovskite oxides, LaAlO 3 exhibits high chemical resistance, high thermal stability, high transparency, high dielectric constant, low toxicity, and good catalytic activity. [12,13] Owing to its surface acidic properties, LaAlO 3 has been investigated for various applications, i.e., Imai and Tagawa et al used it for the oxidative coupling of methane, [14] Wang et al for the degradation of pollutants, [15] Tran et al for hydrogenation and dehydrogenation of hydrocarbons [13] and CO 2 methanation, [13] Mukai et al for steam reforming, [16] Deng et al for far-infrared radiation applications, [17] Shaik et al for drug delivery, [18] and Sato et al for oxidative coupling of methane. [19] Published studies have reported that A-and B-site substitution of LaAlO 3 with various noble and transition metal ions, e.g., A-site with Sr, Ca, Nd, [20][21][22] and B-site with Rh, Ni, Co, Cu, Ga, Cr, Ce, Mn, Pt, Ru, Pd, changes the electrical, catalytic, optical, and magnetic properties by modifying oxygen vacancy concentration, and valance states of elements.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Published studies have reported that A-and B-site substitution of LaAlO 3 with various noble and transition metal ions, e.g., A-site with Sr, Ca, Nd, [20][21][22] and B-site with Rh, Ni, Co, Cu, Ga, Cr, Ce, Mn, Pt, Ru, Pd, changes the electrical, catalytic, optical, and magnetic properties by modifying oxygen vacancy concentration, and valance states of elements. [13,17,[23][24][25] Hashimoto et al reported that the A-site substitution of LaAlO 3 , Sr substitution in La-sites, improved oxygen ionic mobility by inducing the formation of oxygen vacancies; on the other hand, A-site deficiency worsened the oxygen ionic conductivity, perovskite oxide behaved like an ionic insulator. [26] For B-site doping, Anil et al observed improved catalytic activity for the B-site Ru, Pt and Pd (2%) substituted LaAlO 3 .…”
Section: Introductionmentioning
confidence: 99%